Agricultural Cooperation in Libya: A Future Vision (Journal of Academic Research, 2021)
The paper discussed the development of the agricultural cooperative movement in Libya, before and after the issuance of law No. 46 of 1971, which  regulations the work of agricultural cooperatives in Libya, with presentation of the current status of the agricultural cooperative societies in Libya, with an overview of the current situation of agricultural cooperative societies in terms of numbers and numbers of associates and tasks.                                                                                                             The paper highlighted the most important problems constraints  facing the development of agricultural cooperative societies through restructuring them to be an effective structure in  agricultural development. These Include structural problems of the agricultural cooperatives and the instability of the organizional structure of the  agricultural cooperatives structures, as  compared to some successful international experiences in agricultural cooperation represented by the experiences of Japan and India, to benefit from them in the development of agricultural cooperatives for Libya.                                                                                 The recommendations focused on the implementation   mechanisms necessary for the rehabilitation of agricultural cooperatives and the promotion of the cooperative structure in Libya on the basis and principles of international cooperation to achieve agricultural development.